Why Are Women Less Represented in Intracerebral Hemorrhage Trials?. Issue 2 (February 2021) - Greige, Tatiana; Norton, Casey; Foster, Lydia D.; Yeatts, Sharon D.; Thornhill, Andre; Griffin, Jessica; Wang, Jeffrey; Hrdlicka, Courtney M.; Selim, Magdy
Abstract : Background and Purpose: Fewer women than men tend to be enrolled in clinical trials of intracerebral hemorrhage. It is unclear whether this reflects lower prevalence of intracerebral hemorrhage in women, selection bias, or poor recruitment efforts. We undertook this study to examine differences between men and women in the reasons for exclusion from the iDEF trial (Intracerebral Hemorrhage Deferoxamine). Methods: The screen failure log included 29 different reasons for exclusion. Chi-square statistics were used to evaluate the differences in reasons for exclusion between men and women. Results: A total of 38.2% of participants in iDEF were women. Three thousand nine hundred eighty-two women (45.7%) and 4736 men (54.3%) were screen failures ( P <0.0001). Similar proportions of women (1.28%) and men (1.73%) were excluded due to inability to obtain consent ( P =0.1). Patients or families declined participation in 1.26% of women versus 1.31% of men ( P =0.9). More women than men failed screening because of age>80 (22.40% versus 12.61%; adjusted P =0.0007) and preexisting do-not-resuscitate/do-not-intubate (3.69% versus 2.83%; adjusted P =0.067). Conclusions: Lower rates of women enrollment in the iDEF trial may be attributed to older age. Inability to obtain consent or declining participation was similar between women and men, arguing against selection bias. Our findings should be confirmed in other intracerebral hemorrhage trials to determine best strategies to improve women's representation in future trials. Abstract : Supplemental Digital Content is available in the text.